Effects of Power Training on Gait, Power, and Function in Children with Cerebral Palsy. (4th May 2022) - Drumm, Michaella; Fabiano, Julia; Lee, Evelyn; Jezequel, Jennifer; Rao, Ashwini K.; Yoon, Lisa
Abstract: Aims: This scoping review aims to: 1) examine available literature regarding the effects of power training on gait speed, power, and function in ambulatory children with CP and 2) identify the variations in exercise dosage and rehabilitation recommendations for power training and plyometrics in children with CP. Methods: Four databases (PubMed, CINAHL, Embase, and Cochrane) were searched for papers including power or plyometric training with outcome measures for gait, power or functional performance. ES was calculated for RCTs. Cohorts and case series/studies were evaluated qualitatively. Results: Ten articles fit search criteria: four RCTs, three cohort studies, one case series, and two case studies. Power training consistently demonstrated improvements in muscle power compared to its effects on gait and function. ES of mean MPST (W) ranged from 0.36-1.13. 1 MWT and SSGS ES were 1.31 and 1.15, respectively. TUG ES ranged from −0.33 to −2.42. ES for GMFM-66 was 0.13 and 1.11 for Dimension D and Dimension E, respectively. Conclusions: There is limited, but promising evidence to support that power training may improve gait speed, power, and function in children with CP. Future, more robust research is required to examine effects in a larger, diverse population, to determine long-term effects and exercise prescription.